A Hybrid scheme for fault location in unbalanced multi-lateral distribution network with distributed generation. (July 2021) - Kumar, Ranjeet; Saxena, D.
Highlights: Novel hybrid method combining the high-frequency transient and impedance method. High-frequency transients is used for determination of the faulted line section. Faulted line segment is identified using WMM and fault current direction. Exact fault location using the impedance based method. Abstract: Fault location in an unbalancend multi-lateral distribution network having several branches, laterals, load taps and distributed generation is a major challenge. In case of multi-lateral distribution network, the fault location scheme needs to accurately locate the faulted line segment to avoid the problem of multiple fault location candidates. Traditional fault location schemes in such network employs additional measures to filter out the exact fault location out of the multiple candidates. To overcome the above mentioned problem, a new hybrid method combining high-frequency transient method and impedance based method is proposed in this work for fault location in a unbalacened multi-lateral distribution network. This method first identifies the line section with fault after that the impedance based method is utilized to locate the exact fault location. The simulation results obtained demonstrate that the proposed scheme for fault location is capable of locating all shunt fault type with good accuracy. Graphical abstract: Image, graphical abstract